A Review on Vitamin D Deficiency - Shukla, Priya; Kumari, Mamta; Pandey, Mayankesh (Journal for Research in Applied Sciences and Biotechnology, 2023)
Vitamin D is a fat-soluble vitamin that plays an important role in bone metabolism and seems to have some anti-inflammatory and immune-modulating properties. In addition, recent epidemiologic studies have observed relationships between low vitamin D levels and multiple disease states. Low vitamin D levels are associated with increased overall and cardiovascular mortality, cancer incidence and mortality, and autoimmune diseases such as multiple sclerosis. Although it is well known that the combination of vitamin D and calcium is necessary to maintain bone density as people age, vitamin D may also be an independent risk factor for falls among the elderly. Vitamin D had been linked to skeletal disease including calcium, phosphorus, and bone metabolism, osteoporosis, fractures, muscle strength, and falls. In the 2000s, growing scientific attention turned to non-skeletal chronic diseases as vitamin D deficiency was linked to cancer, cardiovascular diseases, metabolic disorders, infectious diseases, and autoimmune diseases, as well as mortality.